2017
DOI: 10.1089/ten.tea.2016.0507
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Protein Binding Influences Heparin-Based Modulation of Spatial Growth Factor Delivery for Bone Regeneration

Abstract: Tissue engineering strategies involving the in vivo delivery of recombinant growth factors are often limited by the inability of biomaterials to spatially control diffusion of the delivered protein within the site of interest. The poor spatiotemporal control provided by porous collagen sponges, which are used for the clinical delivery of bone morphogenetic protein-2 (BMP-2) for bone regeneration, has necessitated the use of supraphysiological protein doses, leading to inflammation and heterotopic ossification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 62 publications
0
54
0
Order By: Relevance
“…BMP-2 release was also notably higher in vivo than in vitro , which may be attributed to fluorophore degradation, differences in detection methods (colorimetric ELISA substrate in vitro vs. fluorescence in vivo ), hydrogel leaking out of the construct into the subcutaneous environment, and the presence of numerous proteases, cells, and heparin-binding proteins that could accelerate BMP-2 release and degradation. We have previously demonstrated that heparin-binding serum proteins can displace BMP-2 bound to HMPs and increase BMP-2 release in vitro [41]; thus, competitive binding of blood-borne proteins to HMPs in vivo may similarly displace BMP-2 and decrease its retention in implanted constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP-2 release was also notably higher in vivo than in vitro , which may be attributed to fluorophore degradation, differences in detection methods (colorimetric ELISA substrate in vitro vs. fluorescence in vivo ), hydrogel leaking out of the construct into the subcutaneous environment, and the presence of numerous proteases, cells, and heparin-binding proteins that could accelerate BMP-2 release and degradation. We have previously demonstrated that heparin-binding serum proteins can displace BMP-2 bound to HMPs and increase BMP-2 release in vitro [41]; thus, competitive binding of blood-borne proteins to HMPs in vivo may similarly displace BMP-2 and decrease its retention in implanted constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the release of BMP-2 from HMPs in serum was used to establish association and dissociation rate constants chosen that accurately described BMP-2-HMP interactions. Rate constants were initially chosen based on literature values for BMP-2 binding to linear heparin (K D = 20 nM, k on = 5.1e-04 1/nM•s, k off = 0.01 1/s) [40] and subsequently adjusted for HMPs using a COMSOL model of in vitro BMP-2-HMP interactions in serum [41], which revealed that a higher dissociation rate constant than that of linear heparin was necessary to accurately model the experimental results (K D = 500 nM, k on = 5.1e-04 1/nM•s, k off = 0.25 1/s). Finally, D BMP,Alg , D BMP,Tiss , and K D were varied by +/−10% to evaluate the sensitivity of the model to changes in these key parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Hettiaratchi et al demonstrated that the release rate of bone morphogenetic protein-2 (BMP-2) from heparin-based microparticles increased in the presence of bovine serum due to competitive protein binding. [59] In another study by Hettiaratchi et al, it was shown that <25% of bound BMP-2 was released from heparin microparticles over 28 days. [60] In this case, BMP-2 bioactivity was conserved.…”
Section: Heparin-based Hydrogels For Growth Factor Releasementioning
confidence: 97%
“…The use of a heparin mesh to bind bone morphogenic protein (BMP)-2 was shown to be an effective method of localizing the BMP-2 delivery in vitro; however, when tested in vivo, it did not work. [62] Competitive binding of serum proteins to the heparin in the mesh negated this effect, allowing BMP-2 to pass beyond the mesh. [62] Heparin sulfate, which is less negatively charged and which shows less generalized affinity than heparin, has been used to mitigate this problem with BMP-2.…”
Section: Immobilization Of Drugs In Hydrogelsmentioning
confidence: 99%
“…[62] Competitive binding of serum proteins to the heparin in the mesh negated this effect, allowing BMP-2 to pass beyond the mesh. [62] Heparin sulfate, which is less negatively charged and which shows less generalized affinity than heparin, has been used to mitigate this problem with BMP-2. [63] More interestingly, this effect has also been specifically used to improve therapeutic outcomes.…”
Section: Immobilization Of Drugs In Hydrogelsmentioning
confidence: 99%